Biodegradability and Acute Biotoxicity Assessment of Pharmaceutical Wastewater by Fe-C Internal Electrolysis Process - Su, Xiaocheng; Liu, Zhi; Zhu, Lin (Asian Journal of Chemistry, 2015)
In order to evaluate the ecological safety and feasibility of internal electrolysis processes for the treatment of pharmaceutical wastewater, the biodegradability and acute biotoxicity were investigated. The results showed that the internal electrolysis did not have a high efficient ability to remove the chemical oxygen demand, but biodegradability of the wastewater was enhanced remarkably and the toxicity was also reduced. Aeration could enhance the removal of chemical oxygen demand, however, the results indicated that biodegradability was enhanced more under anaerobic circumstances besides the biotoxicity. Acidification showed no enhancement on the reduction. The acute biotoxicity increased linearly with the logarithm of wastewater's chemical oxygen demand value, The effluent acute biotoxicity was less than 5 mg Zn2+ L-1 and an average acute biotoxicity cut rate could achieve 35 % no matter the influent chemical oxygen demand.